Pengolahan Limbah Cair Kantin FST Universitas Jambi dengan Memanfaatkan Zeolit dan Eceng Gondok (Eichhornia Crassipes) - Enjelina Situmeang; Zuli Rodhiyah; Tri Syukria Putra (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Liquid waste from the student canteen of FST Jambi University can cause pollution. This study aimed to determine the concentration of COD and oil and fat before and after treatment, and to analyze the effectiveness of zeolite and water hyacinth. The experimental method involved a physical process using zeolite and a biological process using water hyacinth. The initial COD value of the canteen liquid waste was 22,357.28 mg/L, and the oil content was 5,576.12 mg/L. After treatment with zeolite, COD decreased to 2,831.325 mg/L, and oil and fat to 17.92 mg/L. Using a combination of zeolite and water hyacinth for 5, 10, and 15 days, the COD values were 792.25 mg/L, 307.9 mg/L, and 666.67 mg/L, and the oil and fat values were 3.22 mg/L, 6.76 mg/L, and 13.61 mg/L. The effectiveness of zeolite alone resulted in a COD reduction of 87.34% and oil and fat reduction of 99.68%. The combined treatment for 5, 10, and 15 days resulted in COD reductions of 96.46%, 98.62%, and 97.02%, and oil and fat reductions of 99.94%, 99.88%, and 99.76%.